Domains: a new approach to distributed system management - Robinson, D.C.; Sloman, M.S. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
The domain model allows administrators to specify and structure management policies. In doing so, it provides a uniform interface across different functions of management, while being able to scale and handle multiple-organization systems. The need for subdomains and touching domains to provide the flexibility of structuring management necessary to meet the requirements of interorganizational large distributed systems is shown. An example is given to demonstrate the use of the model.< >